2009
DOI: 10.1111/j.1469-7580.2009.01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Semicircular canals and agility: the influence of size and shape measures

Abstract: The semicircular canals of the inner ear sense angular accelerations and decelerations of the head and enable co-ordination of posture and body movement, as well as visual stability. Differences of agility and spatial sensitivity among species have been linked to interspecific differences in the relative size of the canals, particularly the radius of curvature (R) and the ratio of the canal plane area to streamline length (P ⁄ L). Here we investigate the scaling relationships of these two size variables and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 37 publications
4
91
2
1
Order By: Relevance
“…The cochlea functions primarily in hearing, whereas the other structures are associated with spatial orientation and balance. The semicircular ducts detect angular acceleration of the head, and aid in stabilizing vision during motion (summarized by Spoor, 2003;Spoor et al 2007;Cox & Jeffery, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cochlea functions primarily in hearing, whereas the other structures are associated with spatial orientation and balance. The semicircular ducts detect angular acceleration of the head, and aid in stabilizing vision during motion (summarized by Spoor, 2003;Spoor et al 2007;Cox & Jeffery, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Spoor et al 2007;Cox & Jeffery, 2010), and thus can be used to infer agility capabilities in extinct mammals (e.g. Silcox et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Leptictidium is derived from the leptictidan groundplan in having proportionally larger semicircular canals, as evidenced from the morphometric analysis, and its lateral semicircular canal is proportionally larger (relative to other canals) than in the two leptictid species under study (Table 1). This suggests adaptation to faster horizontal head movements and higher agility (e.g., Schmelzle et al 2007;Cox and Jeffery 2010; see discussion below), and may reflect the different hypothesized locomotor adaptations in the postcranial skeleton of European and North American leptictidans. Maier et al (1986) first suggested that Leptictidium was a bipedal runner, not a saltator, because its unfused tibia and fibula and the weak sacroiliac joint (involving only one sacral vertebra) could cause weakness or instability of these joints, which would in turn be inconsistent with saltation.…”
Section: Discussionmentioning
confidence: 99%
“…As Macroscelidea were not included in the original analysis by Spoor et al (2007), we virtually reconstructed the bony labyrinth of an extant specimen of Macroscelides proboscideus (SZ 7397), which has a mean body mass ranging from 38 to 70 g (Silva and Downing 1995); we used the approximate average of 54 g for comparison (Table 1). We also included inner ear measurements by Cox and Jeffery (2010) of the largest living macroscelidean, Rhynchocyon cirnei, in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation